Political Competition when Media Create Candidates' Charisma - Ascensión Andina Díaz (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper studies the location decisions of political parties. We propose a game where agents vote according to ideology and valence, and media create candidates' charisma. The results we obtain show that candidates realize the power of media and therefore locate themselves at some point between the position and the mediam voter and that of the media. However, and more importantly, we further obtain that depending on the media outlets the voters choose to attend, the equilibrium location of candidates may differ. Thus, when voters choose among the outlets, candidates may differentiate their platforms. On the other hand, when voters are exposed to all the outlets in the economy, candidates tend more to moderate their ideology, in an attempt to get the favor of all the media. This result suggests that political competition may end in differentiation if voters only attend to the media that are ideologically close to their convictions. In contrast, political moderation is more easily reached if voters get information from various sources and therefore make more balanced judgements.
Keywords: D72; 330; Charisma; Exposure to media; Political competition; Ökonomische Theorie der Demokratie; Medianwähler-Modell; Theorie; Wahlkampf